2011
DOI: 10.1016/j.ijpharm.2011.05.082
|View full text |Cite
|
Sign up to set email alerts
|

Reversal of multidrug resistance by co-delivery of tariquidar (XR9576) and paclitaxel using long-circulating liposomes

Abstract: One of the major obstacles to the success of cancer chemotherapy is the multidrug resistance (MDR) often resulting due to the overexpression of drug efflux transporter pumps such as P-glycoprotein (P-gp). Highly efficacious third generation P-gp inhibitors, like tariquidar, have shown promising results in overcoming the MDR. However, P-gp is also expressed in normal tissues like blood brain barrier, gastrointestinal track, liver, spleen and kidney. To maximize the efficacy of P-gp inhibitor and reduce the syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
102
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 158 publications
(103 citation statements)
references
References 10 publications
1
102
0
Order By: Relevance
“…Earlier studies have shown that these nano-sized particles, like lipids, micelles, and inorganic hybrid particles, can bypass the P-gp efflux pumps and modify the intracellular accumulation of chemotherapeutic drugs Patel et al, 2011;Li et al, 2012). Multidrug resistance may be treated using a mixture of entrapped cytotoxic drugs and chemo sensitizers.…”
Section: Multidrug Resistancementioning
confidence: 99%
“…Earlier studies have shown that these nano-sized particles, like lipids, micelles, and inorganic hybrid particles, can bypass the P-gp efflux pumps and modify the intracellular accumulation of chemotherapeutic drugs Patel et al, 2011;Li et al, 2012). Multidrug resistance may be treated using a mixture of entrapped cytotoxic drugs and chemo sensitizers.…”
Section: Multidrug Resistancementioning
confidence: 99%
“…[1][2][3][4] In particular, liposomes are well recognized as pharmaceutical carriers because of their biocompatibility, biodegradability, and low toxicity and are clinically used for efficacy enhancement and toxicity reduction. 5,6 Liposomes have good longevity in the blood that allows their accumulation in pathological areas with compromised vasculature, can demonstrate specific targeting to disease sites when various targeting ligands are attached to their surface to enhance intracellular penetration, possess stimulus-sensitivity allowing for drug release from the carriers under certain pathological conditions, and show contrast properties with loading of various contrast materials that allows for direct visualization in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…Patel et al had investigated the co-delivery of ariquidar and PTX into tumor cells to reverse the MDR using long-circulating liposomes. Tariquidar-and PTX-loaded long-circulating liposomes showed significant re-sensitization of the resistant variant for paclitaxel, which could be correlated with an increased accumulation of PTX in tumor cells (Patel et al, 2011). Can et al had developed PEG-PE-based long-circulating micelles co-loaded with elacridar and PTX, and investigated their ability to overcome PTX resistance in two cancer cell lines.…”
Section: Co-delivery Of Photo-thermal Therapy Drugmentioning
confidence: 99%